Pergeseran Tradisi Nanakusa-Gayu bagi Masyarakat Jepang Dewasa Ini - Ainie, Isnin; Irmayanti, Desy; Lesmana, Dika Bhakti (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2023)
Shortly after the New Year celebration (oshogatsu) in Japan, there is a hereditary tradition of serving nanakusa-gayu dishes. Nanakusa-gayu is rice porridge especially served by mixing seven kinds of leaves that are considered sacred by the Japanese. The seven types of leaves include seri, nazuna, hakobera, suzuna, suzushiro, hotokenoza, and gogyou leaves. This research discusses the tradition of eating nanakusa-gayu dishes for Japanese society in this modern era. The method used in this study is descriptive qualitative with data in the form of tweets from social media twitter on January 7, 2023. The results of the research show that there are still many Japanese people who carry out the tradition of eating nanakusa porridge. However, there have been several shifts in tradition, such as the ingredients, when to eat, how to get the ingredients, to the members of the family who participate in eating the nanakusa porridge. In addition, it is also known that there is correlation between the implementation of the nanakusa-gayu tradition with the hope of avoiding various kinds of diseases. This correlation cannot be separated from the activity of picking baby vegetables which is the basic core of the nanakusa-gayu tradition. This activity requires a person to keep moving along the streets while looking for baby vegetables. By doing so, the Japanese will have a healthy body, so they are immune from disease. Keywords: nanakusa-gayu; oseichi ryouri; oshougatsu, tweet.